HUMAN DESTINY IN SHAKESPEARE'S HAMLET AND GOETHE'S FAUST (Multidisciplinary Journal of Science and Technology, 2025)
This article provides an in-depth analysis of the theme of human destiny in Shakespeare's Hamlet and Goethe's Faust. As great works of the Renaissance and Romanticism, they interpret destiny in the dialectic between freedom, determinism, passions, and aspiration. The introduction presents the philosophical and literary significance of the topic, the main parts provide a separate analysis and comparison of each work, and the conclusion provides general conclusions. In the study of this topic in Uzbek literary criticism, textbooks and articles of world literature are used, through which the issue of destiny is considered in a universal and national context. The article draws on literary criticism, psychoanalysis, and philosophical approaches to shed light on the eternal problems of the human condition.